Two Highly Similar Poplar Paleo-subgenomes Suggest an Autotetraploid Ancestor of Salicaceae Plants - Liu, Yinzhe; Wang, Jinpeng; Ge, Weina; Wang, Zhenyi; Li, Yuxian; Yang, Nanshan; Sun, Sangrong; Zhang, Liwei; Wang, Xiyin (Frontiers in Plant Science, 2017)
As a model plant to study perennial trees in the Salicaceae family, the poplar (Populus trichocarpa) genome was sequenced, revealing recurrent paleo-polyploidizations during its evolution. A comparative and hierarchical alignment of its genome to a well-selected reference genome would help us better understand poplar’s genome structure and gene family evolution. Here, by adopting the relatively simpler grape (Vitis vinifera) genome as reference, and by inferring both intra- and inter-genomic gene collinearity, we produced a united alignment of these two genomes and hierarchically distinguished the layers of paralogous and orthologous genes, as related to recursive polyploidizations and speciation. We uncovered homologous blocks in the grape and poplar genomes and also between them. Moreover, we characterized the genes missing and found that poplar had two considerably similar subgenomes (≤0.05 difference in gene deletion) produced by the Salicaceae-common tetraploidization, suggesting its autotetraploid nature. Taken together, this work provides a timely and valuable dataset of orthologous and paralogous genes for further study of the genome structure and functional evolution of poplar and other Salicaceae plants.